STUDI LITERATURE REVIEW PERKEMBANGAN PENELITIAN ASPAL PORUS (TAHUN 2017 – 2021) - Jimmyanto, Hendrik; Firda, Ani; Al Faritzie , Hariman; Fuad, Indra Syahrul; Misdalena, Felly; Lubis, Lega Reskita (LATERAL: Jurnal Teknik Sipil, 2024)
Road pavement is composed of layers that are hardened with a mixture of aggregate and asphalt (flexible pavement) or aggregate and cement (rigid pavement). Each of these types of pavement has a different behavior. Environmental factors such as high rainfall can influence pavement performance where flexible pavement is very susceptible to waterlogging, therefore there is a type of porous asphalt called porous asphalt. This article discusses the results of a literature review of the development of existing porous asphalt from 2017 to 2021 using an international journal database. The results of the literature review show that there are several modifications to the porous asphalt mixture, namely by using rubber materials, polymer materials, fiber materials, and filler materials. Each of these materials produces a different performance. For this reason, further research is needed regarding the use of rubber and fiber materials in modifying porous asphalt mixtures to complete information regarding the development of porous asphalt.